PENGARUH PEMBERIAN JUS JAMBU BIJI DAN TABLET TAMBAH DARAH TERHADAP KADAR HEMOGLOBIN PADA REMAJA PUTRI DI DESA TUNJUK KECAMATAN TABANAN - Ni Made Wancika Maheswari; Ida Ayu Eka Padmiari; I Gusti Agung Ari Widarti (CV. Adiba Aisha Amira, 2026)
Iron supplementation (iron tablets) is a key strategy for preventing anemia among adolescent girls; however, iron absorption is influenced by several factors, including vitamin C intake. Guava juice is rich in vitamin C and has the potential to enhance iron absorption. This study aimed to examine the effect of iron tablet supplementation combined with guava juice on hemoglobin levels in adolescent girls. This study used a quasi-experimental with a pre-test and post-test with control group approach. A total of 40 adolescent girls were divided into two groups: a treatment group that received iron tablets with guava juice and a control group that received iron tablets with mineral water. Hemoglobin levels were measured before and after the intervention. The results showed that the mean hemoglobin level in the treatment group increased from 12.915 g/dL to 14.510 g/dL, while in the control group it increased from 13.770 g/dL to 13.905 g/dL. Paired sample t-test analysis indicated significant increases in both groups (treatment p = 0.000; control p = 0.039). Independent sample t-test results revealed a significant difference between groups (p = 0.024). In conclusion, iron supplementation combined with guava juice is more effective in improving hemoglobin levels than iron supplementation with mineral water.